Impact of Magnetite Nanoparticles Coated with Aspartic Acid on the Growth, Antioxidant Enzymes Activity and Chlorophyll Content of Maize - Mihaela Răcuciu; Andreea Tecucianu; Simona Oancea (MDPI AG, 2022)
In recent decades, magnetite nanoparticles received greater attention in nanobiotechnology due to wide applications. This study presents the influence of the oxidative stress caused by magnetite nanoparticles coated with aspartic acid (A-MNP) of 9.17 nm mean diameter size, on maize (Zea mays) seedlings, in terms of growth, enzymatic activity and chlorophyll content as evaluated in exposed plant tissues. Diluted suspensions of colloidal magnetite nanoparticles stabilized in water were added to the culture medium of maize seeds, such as to equate nanoparticle concentrations varying from 0.55 mg/L to 11 mg/L. The obtained results showed that the growth of maize was stimulated by increasing the level of A-MNPs. Plant samples treated with different concentrations of A-MNP proved increased activities of catalase and peroxidase, and chlorophyll content, as well. The exposure of plants to magnetite nanoparticles may induce oxidative stress, which activates the plant defense/antioxidant mechanisms.